2016
DOI: 10.1093/mnras/stw2833
|View full text |Cite
|
Sign up to set email alerts
|

Non-monotonic spatial distribution of the interstellar dust in astrospheres: finite gyroradius effect

Abstract: High-resolution mid-infrared observations of astrospheres show that many of them have filamentary (cirrus-like) structure. Using numerical models of dust dynamics in astrospheres, we suggest that their filamentary structure might be related to specific spatial distribution of the interstellar dust around the stars, caused by a gyrorotation of charged dust grains in the interstellar magnetic filed. Our numerical model describes the dust dynamics in astrospheres under an influence of the Lorentz force and assump… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…For a more detailed discussion see also Scherer et al (2016b). Although this being the termination shock distance, other authors (del Valle & Pohl 2018;Katushkina et al 2017, among others) call the above distance the standoff distance or the bow shock distance (Meyer et al 2016). The reason why only the TS distance can be determined is the fact that in ideal HD between the TS and the BS Bernoulli's law holds, while in the downstream region of TS and BS the ram (ρv 2 /2) and thermal pressure (P) can be calculated via the Rankine-Hugoniot equations.…”
Section: The Shock and Astropause Distancesmentioning
confidence: 99%
“…For a more detailed discussion see also Scherer et al (2016b). Although this being the termination shock distance, other authors (del Valle & Pohl 2018;Katushkina et al 2017, among others) call the above distance the standoff distance or the bow shock distance (Meyer et al 2016). The reason why only the TS distance can be determined is the fact that in ideal HD between the TS and the BS Bernoulli's law holds, while in the downstream region of TS and BS the ram (ρv 2 /2) and thermal pressure (P) can be calculated via the Rankine-Hugoniot equations.…”
Section: The Shock and Astropause Distancesmentioning
confidence: 99%
“…Recently, Katushkina et al (2017; hereafter Paper I) presented a physical mechanism possibly responsible for the origin of the cirrus-like structure of astrospheres around runaway stars. It was shown that, under proper conditions, alternating minima and maxima of the dust density (seen like filaments) might appear between the astrospheric bow shock (BS) and the astropause (AP) because of periodical gyromotion of the dust grains around the interstellar magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the perpendicular orientation of the ISM magnetic field can result in series of multiple arcs normal to the direction of motion of the star (Fig. 11f) as modelled in the context of hot OB stars in Katushkina et al (2017Katushkina et al ( , 2018, see also Baalmann et al (2021). Furthermore, the opening of the bow shock can significantly differ from a projection model to another, with rounder termination shocks (Fig.…”
Section: Emission Mapsmentioning
confidence: 86%